Reposisi AC Central PT Kraft Ultra Jaya Solusi Praktis untuk Efisiensi Operasional dan Pemeliharaan - Muliawan, Andre Tito; nandar, Kus; Faturrohman, Regi (Universitas Majalengka, 2025)
The rapid growth of industrial technology has led to increasing demand for efficient and environmentally friendly cooling systems. Central air conditioning (AC Central) is widely applied in large buildings such as offices, shopping centers, hotels, and hospitals to ensure thermal comfort and operational effectiveness. This study focuses on the repositioning of a central AC system to evaluate its technical, energy, and operational impacts. The research employed a descriptive case study with a quantitative approach. Data were obtained through direct observation, technical measurements (temperature, humidity, and electricity consumption), documentation of the repositioning process, and interviews with technicians. The repositioning stages included dismantling the indoor and outdoor units, installing condensing unit frames, piping, welding, leak testing using nitrogen, system vacuuming, refrigerant charging with R-407C, and a 12-hour running test. The results indicate that the system successfully achieved the desired room temperature, improved airflow distribution, and facilitated maintenance access without operational disturbances. Furthermore, repositioning was shown to extend component lifespan and potentially reduce maintenance costs. Overall, this study highlights that repositioning central AC systems is an effective strategy to optimize performance, improve energy efficiency, and support sustainability in industrial applications.